URBAN EVERYDAY LIFE IN MILITARY TIME (City: History, Culture, Society, 2018)
Review of Oksana Ovsiyuk's monograph "Life after the Occupation: The Life of Kievans 1943 - 1945". Kyiv: Duliby, 2017
Keywords: review; Kyiv; occupation